PENGEMBANGAN BUKU JURNAL 7 KEBIASAAN ANAK INDONESIA HEBAT UNTUK MEMBENTUK KARAKTER ANAK SEJAK DINI DI TK BILINGUAL ISLAMIC SCHOOL RUMAH ILMU - Sandra Sari, Dewi; Yossi Srianita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aimed to develop a journal book based on the Seven Habits of Great Indonesian Children as a medium for strengthening early childhood character at Rumah Ilmu Bilingual Islamic Kindergarten. The study employed a research and development approach using the ADDIE model, which comprised analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, questionnaires, validation sheets, and child-habituation observation sheets. The product was reviewed by a subject-matter expert, a media expert, and an instrument expert, followed by small-group and large-group trials involving children aged five to six years. The subject-matter and media validations each obtained 97.5%, while the instrument validation obtained 96.4%; all were categorized as highly valid. The small-group trial produced an average score of 75.0%, and the large-group trial produced an average score of 94.75%, indicating that the product could be used well after revisions and repeated assistance. The journal integrates the habits of waking up early, worshipping, exercising, eating healthy and nutritious food, enjoying learning, participating in the community, and going to bed early through child-friendly illustrations and daily monitoring activities. The findings indicate that the journal book is highly feasible as a practical medium for supporting consistent character habituation through cooperation between teachers and parents.